2021
DOI: 10.3389/fonc.2021.617966
|View full text |Cite
|
Sign up to set email alerts
|

Seizures, Edema, Thrombosis, and Hemorrhages: An Update Review on the Medical Management of Gliomas

Abstract: Patients affected with gliomas develop a complex set of clinical manifestations that deeply impact on quality of life and overall survival. Brain tumor-related epilepsy is frequently the first manifestation of gliomas or may occur during the course of disease; the underlying mechanisms have not been fully explained and depend on both patient and tumor factors. Novel treatment options derive from the growing use of third-generation antiepileptic drugs. Vasogenic edema and elevated intracranial pressure cause a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 161 publications
(187 reference statements)
0
15
0
Order By: Relevance
“…In addition, a retrospective study by Gaggero et al (2009) reported that epilepsy is a common symptom in pediatric patients with supratentorial brain tumors, with a high rate of 53.57%. Patients with brain tumors or BM are at risk for intracranial hemorrhage (ICH), which can occur as an early clinical manifestation of brain tumors, or as a complication of cancer treatment (Zoccarato et al, 2021). Wakai et al (1982) conducted a retrospective study and confirmed that spontaneous ICH was observed in 94 out of 1861 patients with brain tumors.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, a retrospective study by Gaggero et al (2009) reported that epilepsy is a common symptom in pediatric patients with supratentorial brain tumors, with a high rate of 53.57%. Patients with brain tumors or BM are at risk for intracranial hemorrhage (ICH), which can occur as an early clinical manifestation of brain tumors, or as a complication of cancer treatment (Zoccarato et al, 2021). Wakai et al (1982) conducted a retrospective study and confirmed that spontaneous ICH was observed in 94 out of 1861 patients with brain tumors.…”
Section: Discussionmentioning
confidence: 92%
“…Glioma-associated edema is considered to be vasogenic and is caused by increased vascular permeability [34]. This vascular permeability is due to immature tumor vessels that are induced by an excessive secretion of angiogenetic factors, such as the vascular endothelial growth factor (VEGF) [35]. VEGF expression is shown to be positively associated with PD-L1 expression in several cancers, including gliomas [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of patients with GBM (22 publications, n = 8752) also showed that steroid treatment was associated with shorter OS (HR: 1.54; 95% CI: 1.37–1.75; p < 0.01) and PFS (HR: 1.28; 95% CI: 1.1–1.49; p < 0.01) [ 21 ]. The difference in survival outcomes may be due to the fact that patients with more severe GBM are more likely to receive steroid treatment, which is the standard of care for decreasing brain edema and for alleviating symptoms such as pain and loss of appetite [ 22 ]. As for methylation status, there were no significant differences in OS or PFS when comparing steroid use with non-use within the methylated cohort or when comparing steroid use with non-use within the unmethylated cohort in this study.…”
Section: Discussionmentioning
confidence: 99%